Adapting to a changing climate: An operational space for local adaptation committee in Santos coastal area - de Freitas, Débora M. [UNESP]; de Carvalho, Danielle Almeida [UNESP]; Hosokawa, Eduardo Kimoto (Springer Nature, 2018)
Coastal living countries are the frontline of climate change impacts presenting vulnerability to natural disasters and other climate hazards. Specially, in developing countries, there is greater vulnerability and environmental risks, related to populous irregular settlements common in coastal areas. The impacts of climate change will materialize over the next century, however by taking action now it is possible to adapted and avoid risks. At the local scale, the impacts are more significant so local government policies play an important role in preventing and managing risks. This chapter summarizes recent research findings in planning and management about climate change adaptation on coastal areas and presents a study case in the coastal city of Santos, Brazil. Based on decision makers and local community perceptions, this chapter analyses the creation of a local policy and points out the importance of a governance structure to manage climate change related decisions. Finding an adequate operational space for adapting to a changing climate in coastal complex regions such as Santos requires local and regional strategies. In this sense, local committees can act as enablers to ensure institutional support for climate adaptation as a priority issue in the political and planning agendas.
Keywords: Climate adaptation; Decision-making; Governance; Local government; Planning; Policy